The Implementation Building Character Based on Islamic Values and the Impact of Resilience on Bullying Victims on Students of Darul Ulum Saleh Jaya Islamic Boarding School - Abdul Karim; Siti Roudhotul Jannah; Ahmad Muslimin (CV. Creative Tugu Pena, 2025)
This study aims to analyze the implementation strategies of character education based on Islamic values in strengthening the resilience of bullying victims among students at Pondok Pesantren Darul Ulum Saleh Jaya, Air Salek Subdistrict, Banyuasin Regency. It also seeks to examine the impact of these strategies on the students' resilience. This research employs a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation, with data validity ensured through source triangulation. The data analysis techniques involved data reduction, data presentation, and conclusion drawing. The findings of the study reveal that: (1) The implementation strategy of character education based on Islamic values at Pondok Pesantren Darul Ulum Saleh Jaya is carried out in a structured manner through discipline, independence, and role modeling to support bullying victims. Core values such as honesty, responsibility, patience, and ukhuwah Islamiyah (Islamic brotherhood) are instilled through social interaction, habituation, and programs such as halaqah, mentoring, and emotional support to enhance victims' self-confidence. (2) The Islamic value-based character education has a positive and effective impact on improving the resilience of bullying victims through education, personalized approaches, and a supportive environment. Values such as patience, sincerity, and empathy contribute to fostering harmony, reducing bullying, and building the students' self-esteem.